2015
DOI: 10.1371/journal.pone.0134823
|View full text |Cite
|
Sign up to set email alerts
|

NMR and MD Studies Reveal That the Isolated Dengue NS3 Protease Is an Intrinsically Disordered Chymotrypsin Fold Which Absolutely Requests NS2B for Correct Folding and Functional Dynamics

Abstract: Dengue genome encodes a two component protease complex (NS2B-NS3pro) essential for the viral maturation/infectivity, thus representing a key drug target. Previously, due to its “complete insolubility”, the isolated NS3pro could not be experimentally studied and it remains elusive what structure it adopts without NS2B and why NS2B is indispensable. Here as facilitated by our previous discovery, the isolated NS3pro has been surprisingly deciphered by NMR to be the first intrinsically-disordered chymotrypsin-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
132
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(145 citation statements)
references
References 58 publications
13
132
0
Order By: Relevance
“…The refolded NS2B-NS3pro with His-tag (column 2 of Fig. We attempted to refold Zika NS3pro without NS2B and found that NS3pro completely precipitated during refolding, thus indicating that Zika NS3pro also absolutely requests its NS2B cofactor for the correct folding, as previously observed on other flavivirus NS3 proteases (12)(13)(14)(15)(16)(17)(18). 1C).…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…The refolded NS2B-NS3pro with His-tag (column 2 of Fig. We attempted to refold Zika NS3pro without NS2B and found that NS3pro completely precipitated during refolding, thus indicating that Zika NS3pro also absolutely requests its NS2B cofactor for the correct folding, as previously observed on other flavivirus NS3 proteases (12)(13)(14)(15)(16)(17)(18). 1C).…”
Section: Resultssupporting
confidence: 57%
“…Cloning, expression and purification of linked and unlinked Zika NS2B-NS3pro-Based on the sequence alignment with NS2B and NS3pro of the Dengue serotype 2 we previously characterized (12), the corresponding Zika sequences were identified for the NS2B (Fig. 1A) and NS3pro (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NS3 localizes to the membranes by interacting with the membrane-localizing transmembrane viral protein NS2B and helps in viral polyprotein processing and viral replication (Falgout et al, 1991; Markoff et al, 1997; Yu et al, 2013). The trypsin-like serine protease activity has been mapped to His53, Asp77, and Ser138 (catalytic triad) (Chambers et al, 1990; Gupta et al, 2015). …”
Section: Zika Virus Genome Organization and Polyprotein Processingmentioning
confidence: 99%